2018
DOI: 10.1007/s11243-018-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures and antimicrobial activities of nickel(II) and zinc(II) diaminomaleonitrile-based complexes

Abstract: Three Ni(II) and Zn(II) complexes [Ni(L1)], [Ni(L2)], and [Zn(L3)(DMSO)] (L1 = 2,3-bis(2-hydroxybenzylideneimino)-2,3-butenedinitrile, L2 = 2,3-bis(2-hydroxy-3-methoxybenzylideneimino)-2,3-butenedinitrile, L3 = 2,3-bis(2-hydroxy-1-naphthylideneimino)-2,3-butenedinitrile) were obtained in DMSO by one-pot syntheses. The complexes were characterized by physicochemical and spectroscopic methods. Also, their solid-state structures were determined by single-crystal X-ray diffraction. The geometries of the Ni(II) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Nevertheless, unlike Cu 2+ , showing a high stability that can be attributed to LFSE obtained through the Jahn-Teller distortion, Zn 2+ has low stability due to a lack of LFSE for its d 10 electronic configuration, and thus has no preference for any specific ligand field geometry. These principles may be an explanation of the differences obtained between these two latter metal complexes in some studies in terms of antimicrobial activities [51,53,58,59,69], where the stronger affinity of Cu(II) for biomolecules could enhance the permeability of the Cu(II) complexes through cell membrane [70]. For instance, considering the large panel of complexes synthesized by Nazirkar et al, Cu(II) complexes possessing higher antibacterial activity against Mycobacteria Tuberculosis showed stronger efficacy compared to their Zn(II) counterparts by a factor of 62.5 [53].…”
Section: Zincmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, unlike Cu 2+ , showing a high stability that can be attributed to LFSE obtained through the Jahn-Teller distortion, Zn 2+ has low stability due to a lack of LFSE for its d 10 electronic configuration, and thus has no preference for any specific ligand field geometry. These principles may be an explanation of the differences obtained between these two latter metal complexes in some studies in terms of antimicrobial activities [51,53,58,59,69], where the stronger affinity of Cu(II) for biomolecules could enhance the permeability of the Cu(II) complexes through cell membrane [70]. For instance, considering the large panel of complexes synthesized by Nazirkar et al, Cu(II) complexes possessing higher antibacterial activity against Mycobacteria Tuberculosis showed stronger efficacy compared to their Zn(II) counterparts by a factor of 62.5 [53].…”
Section: Zincmentioning
confidence: 93%
“…They attributed these enhancements to the greater lipophilic nature of the complexes, which facilitates the penetration through the lipid membrane as discussed above. Additionally, Sheikhshoaie et al showed promising antimicrobial activities, as their square pyramidal Zn(II) complexes had both bacteriostatic and bactericidal effects against a wide range of bacteria and fungi [69]. As shown in these few examples and according to the literature, many copper-based complexes have been designed over the past few decades, possessing different kinds of ligands, substituents and geometries that influence their antimicrobial activities.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the metal complexes have been found to exhibit greater activities as compared to the Schiff base ligand which are a result of the lipophilic nature of the complexes which eases cross-membrane movement. The square pyramidal Zn (II) complexes possess bacteriostatic as well as bactericidal properties against a wide array of bacterial and fungal strains [ 58 ]. A study was conducted to find out antimicrobial potential of Zn (II) complexes, involving ibuprofen with presence of N-donor heterocyclic ligands and with variable shapes and structures.…”
Section: Metal Complex-based Antimicrobial Compoundsmentioning
confidence: 99%
“…Bisimines derived from 2-hydroxy-1-naphthadehyde and their metal complexes are known to have a wide range of biological activity as well as function as fluorescent chemosensors and selective electrodes. [1][2][3][4][5][6][7] The compounds having imine bonds ( C N ) are known by many names such as imines, Schiff bases, azomethines, and salens. Salen-or salophen-type ligands are also called monoimines if they contain a single imine group and bisimines if they contain two imine groups.…”
Section: Introductionmentioning
confidence: 99%